2-D electron system in the RF-discharge plasma. Part I. General observations - Berezhnyj, V.L.; Berezhnaya, I.V. (Вопросы атомной науки и техники, 2018)
The hypothesis is advanced for similarity between the space-charge layers formed by the plasma in the nearantenna region of ICRF discharges and the two-dimensional electron systems created specially for each specific realization for the studies of metals, semimetals and semiconductors. Висувається гіпотеза про аналогічність шарів об’ємних зарядів, що створюються плазмою у приантенній області ICRF-розрядів та двомірних електронних систем, які виготовляються спеціально в кожній конкретній реалізації для дослідження металів, напівметалів та напівпровідників. Выдвигается гипотеза об аналогичности слоев объемных зарядов, образуемых плазмой в приантенной области ICRF-разрядов и двумерных электронных систем, создаваемых специально в каждой конкретной реализации для исследования металлов, полуметаллов и полупроводников